Sertifikat Lestari PT. Diamond Raya Timber: Aset atau Beban? - Ahmad Maryudi (Jurnal Ilmu Kehutanan, 2007)
Sustainable Certificate of PT Diamond Raya Timber: Asset or Liability?Several environmental non-government organizations and green parties pursue various strategies to promote sustainable management of forest resource. Due to the increasing environment awareness of some segments of timber users, they have established a certification body and developed a set of criteria and indicators, against which the performance of participating forest companies will be assessed. Early experiences in Indonesia showed that certification received warm welcome from several forest companies, as there is no question that they saw the attraction of being certified. However, it appears that their enthusiasm was dampened by the experience of a certified company. Certification might have been seen as more of a liability than an asset as the economic benefits from market access became less clear, while the costs became more apparent. The use of rigid standards might result in “negative” responses from forest companies. More proactive approaches might encourage the companies to join certification.